Hormonal regulation of lipogenesis. - Gathercole, L; Morgan, SA; Tomlinson, J (2013)
Obesity has reached epidemic proportions with severe heath consequences including type 2 diabetes, nonalcoholic fatty liver disease, and premature cardiovascular mortality. Understanding the biological processes that govern fat deposition in a tissue-specific manner is therefore crucial if we are to try to design novel and efficacious treatments that might limit fat accumulation and improve metabolic phenotype and clinical prognosis. Lipid accumulation within a given cell type represents a balance between synthesis, mobilization, and utilization. Common endocrine conditions characterized by hormonal excess and deficiency are often associated with profound abnormalities in body composition and fat deposition. This undoubtedly reflects the complex regulation of lipid metabolism by endocrine factors. In this review, we will outline the current literature that has investigated the hormonal regulation of lipogenesis. This is a complex field, and in many studies, its assessment has been oversimplified with a focus on individual hormones acting in isolation and this bears little relationship to the in vivo situation where multiple hormones act in concert. Further, regulation may be different between rodents and humans and this will be explored. Limitation of lipid accumulation still represents a valid therapeutic target, and it is possible that manipulation of hormonal action has the potential to offer a new therapeutic horizon.